Code to zero - Follett, Ken. (New York Dutton, 2000)
January, 1958-the darkest hour of the cold war and the early dawn of the space race. On the launch pad at Cape Canaveral sits America's best hope to catch up with the Russians-the Explorer I satellite. But at the last moment, the launch is delayed due to weather, even though everyone can see it is a perfectly sunny day. The real reason for the delay rests deep in the mind of NASA scientist who has awoken that morning to find his memory completely erased. Knowing only that he's being followed and watched at every turn, he must find the clues to his own identity before he can discover who is responsible. But even more terrible is the dark secret that they wanted him to forget. A secret that can destroy the Explorer I-and America's future...
Keywords: Space flight -- Fiction; Scientists -- Fiction; Amnesia -- Fiction; Suspense fiction; Science fiction